Busca e avaliação de potenciais inibidores do complexo ZIKV_NS2B-NS3Pro como candidatos a antivirais contra a Febre Zika - Paula, Otavio Rodrigues de (Universidade Federal de São Carlos, 2025)
The Zika virus (ZIKV) was first isolated in 1947 in Uganda, and the first record of human infection by the virus was made 5 years later in Nigeria. The first major outbreak occurred in French Polynesia, where 183,000 people were infected by the virus. Between 2014 and 2015, the virus began to circulate in Brazil, with more than 1 million suspected cases reported and associated with more serious conditions such as microcephaly and Guillain-Barré syndrome. There are still no commercially available vaccines or specific treatments for Zika Fever, and considering the possibility of a new epidemic, the search for treatments remains urgent. One possibility is the development of inhibitors of proteins essential for the viral replication cycle, such as ZIKV protease (ZIKV_NS2B-NS3Pro). In this study, two sets of compounds were evaluated for their inhibitory potential against ZIKV protease. For this purpose, the enzyme was expressed, purified and evaluated for the ideal protein concentration to be used in subsequent assays. Subsequently, an enzyme kinetics assay was performed, from which it was verified that the protein behaved as expected and then inhibition tests could be performed. Initially, a punctual activity inhibition test was performed at a concentration of 200 μM of each compound and those that exhibited significant inhibition were then tested again through serial dilution of 10 points initially at 200 μM. The compounds capable of inhibiting ZIKV protease and more than 80% had their IC50 determined in order to understand whether they were promising as potential anti-Zika agents. The purification protocol of the ZIKV_NS2B-NS3Pro complex proved to be reproducible, providing satisfactory enzyme concentrations. The enzyme kinetics assays, in turn, presented consistent results when compared with the literature. The spot activity assays initially revealed 7 compounds capable of inhibiting the proteolytic activity of the ZIKV_NS2B-NS3Pro complex by 80% in vitro. LSPN 921, LSPN 1070, LSPN 1111, LSPN 1112 and LSPN 1121 proved to be good inhibitors of ZIKV_NS2B-NS3Pro. Among them, LSPN 1111 stands out for its IC50 of 0.4 μM. In view of the results presented, the structural optimization of these compounds identified here may contribute to the development of effective antivirals against flaviviruses, representing a promising approach in the search for new therapies.
Search and evaluation of potential inhibitors of the ZIKV_NS2B-NS3Pro complex as antiviral candidates against Zika Fever
Keywords: Zika; Antivirais; Inibidores; Protease; CIENCIAS BIOLOGICAS::BIOQUIMICA::BIOLOGIA MOLECULAR